Atom absorption energy directed symmetry-breaking synthesis of Au-Ag hierarchical nanostructures and their efficient photothermal conversion - Zeng, Pan (2023)
Asymmetric plasmonic hierarchical nanostructures (HNs) are of great significance in optics, catalysis, and sensors, but the complex growth kinetics and lack of fine structure design limit their practical applications. Herein, a new atom absorption energy strategy is developed to achieve a series of Au-Ag HNs with the continuously tuned contact area in Janus and Ag island number/size on Au seeds. Different from the traditional passive growth mode, this strategy endows seed with a hand to capture the hetero atoms in a proactive manner, which is beyond the size, shape, and assembles of Au seed. Density functional theory reveals ththe adsorption of PDDA on Au surface leads to lower formation energy of Au-Ag bonds (-3.96 eV) than FSDNA modified Au surface (-2.44 eV). The competitive adsorption of two ligands on Au seed is the decisive factor for the formation of diverse Au-Ag HNs. In particular, the Au-Ag2 HNs exhibit outstanding photothermal conversion capability in the near-infrared window, and in vivo experiments verify them as superior photothermal therapy agents. This work highlights the importance of the atom absorption energy strategy in unlocking the diversity of HNs and may push the synthesis and application of superstructures to a higher level.